Self-Worth Level among Students of Practical Courses at School of Physical Education at Yarmouk University - Tilfah, Yaser Mohamad; Melhem, Mohammad Amein; Bani Hani, Anan Hussein (Dirasat: Educational Sciences, 2022)
Objectives: The current study aims to identify the level of self-worth among students of practical courses at School of Physical Education at Yarmouk University. Methods: The study relies on a descriptive design. The sample of the study consisted of (183) students (89 males and 94 females) who are registered in the second semester of the academic year 2019/2020 at Yarmouk Universisty. The sample was selected using a stratified random sampling method. To achieve the objectives of the study, the Self-Worth Scale developed by Krocker, Luttanen and Cooper (2003) was used. Results: The results of the study show that the level of self-worth among students of practical courses at School of Physical Education at Yarmouk University was high. Moreover, there were no statistically significant differences in the level of self-worth due to gender, income level or academic achievement. Conclusions: Based on the results above, the researchers recommend developing training programs to employ family support, competition, and academic competence in order to raise self-worth levels.